Effectiveness of Using Smart Board Media to Improve the Ability to Recognize Alphabets in Children with Class II Autism Spectrum Disorders at SLB Negeri 1 Harau - Yelmayenti, Egi; Arnez, Gaby (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research was motivated by problems that researchers found at SLB Negeri 1 Harau class II. One of the GSA children who doesn't yet know all the alphabets, the letters he doesn't know yet are (j, l, t, v and w). This research aims to see whether the use of smart board media is effective as a solution in improving the ability to recognize the alphabet in GSA children. This research uses a quantitative approach with experimental methods in the form of Single Subject Research (SSR) with an A-B-A design. The results of this research can be seen in 3 conditions. First, the baseline condition (A1) was carried out 3 times with a stable percentage result of 40%. The two intervention conditions (B) were carried out 7 times with a stable percentage of 86%. The three baseline conditions (A2) were carried out 3 times with a stable percentage result of 86%. Based on the results of this research, it can be concluded that the use of smart board media is effective in improving the ability to recognize the alphabet for GSA children.